Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

IF CosX=SinX=[squareroot]?2.SinX P T CosX-SinX=[squareroot]?2.SinX

Asked by chethan U 22nd July 2012, 7:03 PM
Answered by Expert
Answer:
Answer : Given : cosX+ sinX = (underroot2 )*cosX 
To prove : cosX - sinX = (underroot2 )*sinX
 
we have ,
=> (cosX+sinX)2 + (cosX -sinX) = 2
=> ( (underroot 2 ) *(cosX) ) + (cosX-sinX)= 2  { using given equation}
=> 2cos2 X+ (cosX-sinX)= 2  
=> (cos- sinX)= 2 - 2cos2 X
=> (cosX - sinX)= 2 ( sin2X )    { using 1 - cos2 X = sin2A }
 
taking the square root both the sides we get ,
 
=>  cos-  sinX = (underroot2 )*sinX
            Hence Proved 
Answered by Expert 22nd July 2012, 8:54 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp